Truth: an elusive trait in literary trials and in the movies - Zolezzi Ibárcena, Lorenzo (2020)
The purpose of this article is to present eight ways by which it is not possible to find out the truth that lies behind different trials. The cases have been taken from Literature and the movies, as far as these express the legal culture of the population and of the legal actors. Truth is elusive, even though the trial needs social legitimacy and it is obtained the closer to the facts, or the truth, is the outcome of the trial.